2015
DOI: 10.1088/1367-2630/18/1/013008
|View full text |Cite
|
Sign up to set email alerts
|

The simplest causal inequalities and their violation

Abstract: In a scenario where two parties share, act on and exchange some physical resource, the assumption that the parties' actions are ordered according to a definite causal structure yields constraints on the possible correlations that can be established. We show that the set of correlations that are compatible with a definite causal order forms a polytope, whose facets define causal inequalities. We fully characterize this causal polytope in the simplest case of bipartite correlations with binary inputs and outputs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
218
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 125 publications
(223 citation statements)
references
References 45 publications
(143 reference statements)
4
218
1
Order By: Relevance
“…Using the see-saw algorithm, we optimized W ext for a violation of the simplest causal inequalities [4]. We found that W ext is able to violate (by about´-8 10 5 ) the GYNI inequality (9), which proves that W opt is not extensibly causal.…”
Section: Relationship To Extensibly Causal Processesmentioning
confidence: 98%
See 4 more Smart Citations
“…Using the see-saw algorithm, we optimized W ext for a violation of the simplest causal inequalities [4]. We found that W ext is able to violate (by about´-8 10 5 ) the GYNI inequality (9), which proves that W opt is not extensibly causal.…”
Section: Relationship To Extensibly Causal Processesmentioning
confidence: 98%
“…For the scenario where Alice (Bob) has an input bit x (y) and outputs one bit a (b), one causal inequality is a bound on the probability of success of the 'guess your neighbor's input' (GYNI) [4]:…”
Section: Causal Nonseparability and Causal Inequalitiesmentioning
confidence: 99%
See 3 more Smart Citations